The Sociology of Anthony Giddens - Steven Loyal (Pluto Press, 2003)
Few would object to the view that Anthony Giddens is Britain’s foremost sociologist. The recent publication of a four-volume book set dedicated to his writings shows that his work not only carries an intrinsic significance, but perhaps, more importantly, that it continues to exert a considerable theoretical influence on the direction and development of British sociology in general (Bryant and Jary 1997). Previous critiques of Giddens’s sociological works have tended to focus on the formal concepts and ideas underlying his contributions to the subject. In this respect this book offers nothing new. However, this emphasis on the abstract architecture of his work underplays the dynamic character of his texts and fails to elucidate the broader social and political rationale underlying his approach. This book seeks to fill this lacuna by focusing on the developmental nature of Giddens’s work drawing sparingly upon the sociology of knowledge. In contrast to immanent ahistorical approaches, the intention here has been to elaborate the historical emergence, structure and direction of sociological knowledge in relation to group dynamics and political interests.1 The central argument of this book is that Giddens’s sociology needs to be placed within the social, political and historical context within which it was constructed. His theoretical project makes sense only as part of a wider world-view which centres on an attempt to renew a progressive form of liberalism. The distinctive pattern of theoretical innovation, the eclectic derivation and combination of concepts, the inclusion and exclusion of certain principles and ideas, as well as the theoretical inconsistencies and contradictions which arise in consequence, derive ultimately from this commitment to progressive liberalism. Placing his ideas in a context of a broader political worldview allows us to make sense of a pronounced shift in the content of his work after 1989, in addition to his most recent and most overtly political work on the ‘Third Way’ – work which has served as both a basis for and a rationalisation of Tony Blair’s politics. Although this study is primarily concerned with Giddens’s structuration theory, it also incorporates an analysis of his work on modernity and politics, arguing for the interconnection of all three.